Evaluation of parasite contamination on toothbrushes in children in Southeastern Brazil. - Caldeira, François Isnaldo Dias (2022)
Introduction: The toothbrush is an important object for the hygiene of the oral cavity and an effective mechanism to remove the oral waste. Objective: To evaluate the perception of care, storage and parasitic contamination of toothbrushes in children with special health care needs (CSHCN) and children without special health care needs (CWSHCN) in Southern of Minas Gerais State. Material and Methods: This is an observational cross-sectional non-randomized study. The population consisted in 54 children, with age between 7 and 14 years. The questionnaire was distributed to patients to evaluate the perception of care and storage of children’s toothbrushes. Investigation of toothbrushes contamination was performed by parasitological examination and real-time polymerase chain reactions. Results: Regarding the procedures performed after brushing, 50.0% of children with special health care needs (CSHCN) and 56.3% of children without special health care needs (CWSHCN) report washing their brush bristles with water (p <0.001). Both groups did not use an antiseptic solution on toothbrushes. 73.3% of (CSHCN) and 58.7% of (CWSHCN) answered that they use some protection (brush holder and bathroom cabinet) to avoid exposure of brushes to the environment (p <0.001). Conclusion: The children investigated by the study presented good conditions of care and storage of their toothbrushes. No contamination by pathogenic parasites was found during the study period.